2003
DOI: 10.1053/jhep.2003.50014
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide overproduction in megamitochondria of troglitazone-treated human hepatocytes

Abstract: Troglitazone has been withdrawn from therapeutic options for diabetes mellitus because of its severe hepatocyte toxicity of unknown pathogenesis. The aim of the present study was to assess both morphologic and functional alterations in the mitochondria of troglitazonetreated hepatocytes. A polarized human hepatocyte cell line, OUMS-29, was used in this study. The mitochondrial volume and the mitochondrial transmembrane potential (⌬⌿ m ) were examined using flow cytometry with nonylacridine orange (NAO) and rho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 58 publications
6
36
0
Order By: Relevance
“…**p<0.01 and ***p<0.001 vs control. Co Control, Tro troglitazone reports have shown that TZDs affect mitochondrial function and lower ATP production in human hepatocytes and H-2K b muscle cells [11,12,40,41]. Here, we extend these results by demonstrating that troglitazone induces acute mitochondrial membrane depolarisation, activates AMPK and accelerates glucose flux in muscle cells.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…**p<0.01 and ***p<0.001 vs control. Co Control, Tro troglitazone reports have shown that TZDs affect mitochondrial function and lower ATP production in human hepatocytes and H-2K b muscle cells [11,12,40,41]. Here, we extend these results by demonstrating that troglitazone induces acute mitochondrial membrane depolarisation, activates AMPK and accelerates glucose flux in muscle cells.…”
Section: Discussionsupporting
confidence: 75%
“…Unfortunately, troglitazone had rare but serious side effects causing subacute irreversible liver injury and failure [9] and was recently removed from the market [10]. In studies geared to uncover the cause of the hepatotoxicity using human or rat hepatocyte cell lines, several mitochondrial abnormalities were observed including the collapse of the mitochondrial membrane potential [11,12]. In those studies, the effect of troglitazone on mitochondrial membrane potential was rapid (within an hour) and occurred at concentrations approximating those considered therapeutically active.…”
Section: Introductionmentioning
confidence: 99%
“…This inferred conclusion will be based on an analysis of this case series and is also powerfully supported by cellular in-vitro studies and animal experiments [14][15][16][17]. The opposite premise, taken by some, which claims that this animal and cellular data are not relevant to the human experience, is far harder to defend.…”
Section: The Role Of Mitochondrial Dysfunctionmentioning
confidence: 74%
“…These mitochondrial changes were inhibited by N-acetyl cysteine [15]. Furthermore, enhanced susceptibility to cell injury in conditions of preexisting oxidative stress/mitochondrial impairment has been demonstrated by Ong and Boelsterli in a mouse model of silent mitochondrial abnormality [44].…”
Section: Reactive Metabolite/reactive Oxygen Species (Ros)mentioning
confidence: 79%
“…In fact, inhibition of complex I with rotenone or phytanic acid strongly enhances O 2 Ϫ generation. 38 A number of authors have reported that troglitazone produces mitochondrial changes in a hepatocyte cell line 39 and in HepG2 cells. 40 Scatena et al 41 and Brunmair et al 42 have demonstrated that PPAR-ligands decrease respiratory control, induce uncoupling of the oxidative phosphorylation, and reduce the activity of complex I in cell culture and tissue homogenates.…”
Section: Discussionmentioning
confidence: 99%